From small town to legal counsel: a journey of exploration and growth / Mohamed Hafiq Hasan Basri - Hasan Basri, Mohamed Hafiq (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Born and raised in the quaint town of Klang, Selangor, my journey into the world of law began without any prior exposure or familial influence in the legal field. Unlike many aspiring lawyers, I did not grow up amidst legal discussions or courtroom dramas at the dinner table. Instead, my early aspirations leaned towards a different spotlight: journalism. From a young age, I was captivated by the allure of journalism, a world where storytelling meets public scrutiny, where charisma and communication skills reign supreme. Back then, the glitz and glamour of television personalities mesmerized me, prompting a desire to step into their shoes. Of course, this was before the era of social media platforms like Tik Tok and Instagram; television was the pinnacle of media influence, and 1 was drawn to its alluring appeal.